Arte de guerrilha no Brasil ditatorial: O caso das produções de Cildo Meireles e Hélio Oiticica pela via filosófica de Giorgio Agamben (Palíndromo, 2013)
This article aims to analyze some artworks by Cildo Meireles and Hélio Oiticica during the cultural resistance period in dictatorial Brazil (1964-1985). To do so we will take in account the period of Brazilian military dictatorship as a time of state of emergency, so well conceptualized by Italian philosopher Giorgio Agamben, which we will use in this article. We intend to get to a better understanding about the guerrilla art by Cildo Meireles and Hélio Oiticica during dictatorial Brazil.
Keywords: Cildo Meireles; Hélio Oiticica; military dictatorship; Giorgio Agamben